RockOn Workshop - Dirienzo, William; Kisiolek, Ryan (Proceedings of the Wisconsin Space Conference, 2017)
RockOn is a sounding rocket payload building workshop organized by the Colorado Space Grant Consortium, Virginia Space Grant Consortium, and the National Aeronautics and Space Administration's Wallops Flight Facility (WFF). Participants spend a week at WFF building, testing, and integrating a predesigned payload from a kit and see it launched at the end of the week. We attended the workshop with the support of the Wisconsin Space Grant Consortium and report our experience here. We recommend this program to others and plan to participate in the next level of the program, RockSat-C, this year.